High-efficiency solution-processed OLED based on trivalent europium complex by modifying the composition of the multiple-host system - Li, Xiaofang; Yin, Jiaxuan; Wang, Jingyu; Wu, Ruixia; Li, Shuaibing; Sun, Weidong; Zhou, Liang (Frontiers in Chemistry, 2022)
In this work, di-[4-(N,N-ditolylamino)-phenyl]cyclohexane (TAPC); 4,4′,4″-tri (9-carbazoyl)triphenylamine (TcTa); 9-(4-tert-butylphenyl)-3,6-bis(triphenylsilyl)-9H-carbazole (CzSi); and 1,3,5-tri (m-pyrid-3-yl-phenyl)benzene (TmPyPB) were used to constitute the multiple-host system and fabricate solution-processed organic light-emitting diodes (s-OLEDs) with europium complex Eu(DBM)3Phen (DBM, 1,3-diphenylpropane-1,3-dione; Phen,1,10-phenanthroline) as emitter. In order to determine the optimal composition of the multiple-host system, a series of devices with different light-emitting layers (EMLs) were fabricated and compared. Experimental results revealed that removing TmPyPB out of the multiple-host system greatly reduces the turn-on voltage, whereas the addition of TcTa to the multiple-host system helps facilitate the transfer of holes from TAPC to Eu(DBM)3Phen molecules, thus increasing the recombination probability of carriers on emitter molecules. Finally, high performance solution-processed red OLED (turn-on voltage of 3.8 V) based on the europium complex doped multiple-host system obtained the maximum current efficiency of 2.07 cd A−1, power efficiency of 1.54 lm W−1, external quantum efficiency of 1.2%, and brightness of 945 cd m−2.